ATLAS OF NORTHEASTERN YIDDISH: IMPORTANCE OF MAPS IN LINGUISTIC RESEARCH - Beconytė, Giedrė; Katz, Dovid (Geodesy and cartography (Vilnius), 2011)
The paper introduces the application of cartographic methods to research on a culture at the last moment of its in situ existence. The atlas in progress seeks to determine the historic external borders, the internal differentiation and the cultural and linguistic structure and characteristics of Líte ([lítə] - the territory of traditional jewish Lithuania (coterritorial with today's Lithuania, Latvia, Belarus, and swaths of northeastern Poland, northern and eastern Ukraine and westernmost Russia). The main linguistic data were initially organized by lists of locations where use of a particular form had been documented. Sparse information has been converted to a relational database model, linked to geographic data (locations) and analyzed. The discovered information was sufficient to approximately locate spatial clusters that were not thought to be recoverable when the project was initiated. The results of the geographic analysis are presented in the form of maps in the evolving draft of Litvish: An Atlas of Northeastern Yiddish that is accessible for preview at http://www.dovidkatz.net/WebAtlas/AtlasSamples.htm . The structure of the linguistic database also enables publication of the data as a web service representing the location of occurrences of linguistic forms on a larger scale map. However, the small scale linguistic maps represent characteristics of the dialect areas that are more convenient for readers who specialize in the relevant language and culture, but are not familiar with geospatial technologies.